(untitled) (Kronika Bydgoska, 2017)
During the times of the Duchy of Warsaw, many famous and notable people of the Napoleonic era passed through Bydgoszcz. They included Napoleon I Bonaparte, Emperor of the French and Prince Józef Poniatowski. These were brief visits. The former one stopped in Bydgoszcz on July 15, 1807 on his way from Konigsberg to Dresden. The latter one visited the city on August 20, 1810. Both guests received a warm welcome in Bydgoszcz. We know how their visits looked like primarily from newspapers. Finding out more details about these events can become a valuable contribution to comprehensive research on celebrations and cultural events in Bydgoszcz during the period of the Duchy of Warsaw.